1995
DOI: 10.18474/0749-8004-30.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Colored Sticky Traps for Monitoring Thrips Populations (Thysanoptera: Thripidae) in Staked Tomato Fields

Abstract: The response of flower thrips, Frankliniella spp., to various colors and sticky trap designs was evaluated in staked tomato fields in western North Carolina. Yellow sticky traps caught significantly more thrips compared with blue or white traps. There were no differences in the relative proportion of thrips species caught on different colored traps. The size of the flower sampling unit (i.e., 10-flowers versus all flowers per plant) did not influence the correlation between sticky trap catches and thrips abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 0 publications
1
28
0
5
Order By: Relevance
“…We tested white (Gempler'st, Belleville, MI 53508, USA), blue and yellow (both Disposable Stiky Stripst, Olson Products, Medina, OH 44285, USA). These colors were selected for their known attractiveness to various thrips species (Cho et al, 1995;Vernon and Gillespie, 1990;Childers and Brecht, 1996). Clear plexiglass rectangles were coated with Tangle-Trap (The Tanglefoot Company, Grand Rapids, MI 49504, USA) and used as controls to determine capture rates of thrips due to random aerial interception.…”
Section: Sticky Card Selection Plexiglass Controls and Spectral Anamentioning
confidence: 99%
See 3 more Smart Citations
“…We tested white (Gempler'st, Belleville, MI 53508, USA), blue and yellow (both Disposable Stiky Stripst, Olson Products, Medina, OH 44285, USA). These colors were selected for their known attractiveness to various thrips species (Cho et al, 1995;Vernon and Gillespie, 1990;Childers and Brecht, 1996). Clear plexiglass rectangles were coated with Tangle-Trap (The Tanglefoot Company, Grand Rapids, MI 49504, USA) and used as controls to determine capture rates of thrips due to random aerial interception.…”
Section: Sticky Card Selection Plexiglass Controls and Spectral Anamentioning
confidence: 99%
“…Trap attractiveness and capture rates of thrips vary according to species or guild groupings (Kirk, 1984), trap color (Beckham, 1969;Childers and Brecht, 1996;Cho et al, 1995;Vernon and Gillespie, 1990;Walker, 1974;Yudin et al, 1987), U.V. remittance and fluorescence , trap size and shape (Cho et al, 1995;Coli et al, 1992;Moreno et al, 1984;Lewis, 1959), placement height of traps , sunlight degradation of colors (Childers and Brecht, 1996;Samways, 1986;Grout and Richards, 1990), cardinal direction (Beavers et al, 1971), and geographic latitude (Grout and Richards, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…and M. invisa attracted S. dorsalis to come, occupy, and possibly breed on the weed. Color attraction research on S. dorsalis revealed that yellowish-green and yellow were the most preferred color compared to blue and white (Tsuchiya et al 1995;Cho et al 1995;Chu et al 2006). Suitable nutrient in term of availability and composition was also another consideration causing S. dorsalis to prefer certain weed species.…”
Section: Desmanthus Leptophyllusmentioning
confidence: 99%